Exploring best practices of Technical and Vocational Education and Training (TVET) teachers in the 4th Industrial Revolution (4IR) - Mustakim, Siti Salina; Sulaiman, Tajularipin; Abdul Manaf, Umi Kalthom; Minghat, Asnul Dahar; Rabindarang, Siva (Vasile Goldis Western University of Arad, 2021)
This paper exploresthe best practices among TVET teachers in the 4th Industrial Revolution in line with the implementation of the Strategic Plan of Transformation in Vocational Education (SPTVE)2011-2025.Two case studies from two technical institutions that offerTechnology Electronic Courses were conducted.A total number of 16 TVET teachers with more than five years of teaching experiencewere selected purposively for the study. Data gathered from a semi-structuredinterview indicated that some considerationsaboutbest practices are related to the application of visualizationmethods, accelerated learning approach, the strength of a teacher, applications of projects, knowledge sharing, students-centered-learning and guided learning and the use of real equipment or tools. While keeping up with best practices is illustrated in the utilization of the internet and mass media, information digging activities, joining seminars, and sharing experiencesfor a real-life situation. It is suggested that TVET teachers begin to model best practices applied during SPTVE implementation and embed content and teaching principles in the classroom instruction.